Bluebelle pilot randomised controlled trial of three wound dressing strategies to reduce surgical site infection in primary surgical wounds - Blazeby, Jane (BMJ Open, 2020)
OBJECTIVE: Surgical site infection (SSI) affects up to 25% of primary surgical wounds. Dressing strategies may influence SSI risk. The Bluebelle study assessed the feasibility of a multicentre randomised controlled trial (RCT) to evaluate the effectiveness and cost-effectiveness of different dressing strategies to reduce SSI in primary surgical wounds. DESIGN: A pilot, factorial RCT. SETTING: Five UK hospitals. PARTICIPANTS: Adults undergoing abdominal surgery with a primary surgical wound. INTERVENTIONS: Participants were randomised to ‘simple dressing’, ‘glue-as-a-dressing’ or ‘no dressing’, and to the time at which the treatment allocation was disclosed to the surgeon (disclosure time, before or after wound closure). PRIMARY AND SECONDARY OUTCOME MEASURES: Feasibility outcomes focused on recruitment, adherence to randomised allocations, reference assessment of SSI and response rates to participant-completed and observer-completed questionnaires to assess SSI (proposed primary outcome for main trial), wound experience and symptoms, and quality of life (EQ-5D-5L). RESULTS: Between March and November 2016, 1115 patients were screened; 699 (73.4%) were eligible and approached, 415 (59.4%) consented and 394 (35.3%) were randomised (simple dressing=133, glue=129 and ‘no dressing’=132). Non-adherence to dressing allocation was 2% (3/133), 6% (8/129) and 15% (20/132), respectively. Adherence to disclosure time was 99% and 86% before and after wound closure, respectively. The overall rate of SSI (reference assessment) was 18.1% (51/281). Response rates to the Wound Healing Questionnaire and other questionnaires ranged from >90% at 4 days to 68% at 4–8 weeks. CONCLUSIONS: A definitive RCT of dressing strategies including ‘no dressing’ is feasible. Further work is needed to optimise questionnaire response rates. TRIAL REGISTRATION NUMBER: 49328913; Pre-results.